2019
DOI: 10.1186/s40691-019-0183-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 10,12-pentacosadiynoic acid on the morphology and characteristics of electrospun PDA/PU nanofibers

Abstract: The conjugated polymers studied as materials of biosensors are sensitive to external stimuli. The conjugated polymer is superior in thermal properties to low molecular weight materials and is widely used as a material for detecting heavy metals, and noxious gas because it is easily applied to thin films and the like (Son et al. 2015). Polydiacetylene (PDA) is a conjugated polymer that has an intersection between a double bond and a triple bond. In addition, PDA can be synthesized easily by polymerizing diacety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Thus, the ratio of 3:1 (PVP:PDA) with 4% polymer concentration was selected as the optimum condition for the most uniform fibers with the smallest diameter. During electrospinning and solvent evaporation, the self‐assembly of PCDA occurred, and then UV irradiation resulted in the photopolymerization of PCDA through conjugation with a color change from white to blue, as reported earlier 25 …”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Thus, the ratio of 3:1 (PVP:PDA) with 4% polymer concentration was selected as the optimum condition for the most uniform fibers with the smallest diameter. During electrospinning and solvent evaporation, the self‐assembly of PCDA occurred, and then UV irradiation resulted in the photopolymerization of PCDA through conjugation with a color change from white to blue, as reported earlier 25 …”
Section: Resultssupporting
confidence: 61%
“…It was found that PDAs typically absorb light with 650 nm wavelength indicating a blue color. Upon exposure to external stimuli, the color of PDA turns to red with absorption change to 550 nm 25 . When the fibers are heated, a reflectance switch to a lower wavelength occurs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, most commercial polyols are derived from petrochemicals; however, concerns about environmental pollution and regulations have led to an interest in using sustainable resources to replace petroleum-based polyols [ 8 ]. The most common sustainable bio-based materials are vegetable oils, polysaccharides, cellulose, lignocellulose, and starch [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Among them, vegetable oils have attracted considerable attention as an alternative to petroleum-based commercial polyols because of their abundance, price competitiveness, low toxicity, inherent bio-degradability, and ease of extraction from bio-renewable resources such as castor [ 17 ], soybean [ 18 ], canola seeds [ 19 ], sunflower [ 20 ], grapeseed [ 21 ], palm [ 22 ], and others [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The absorption spectra of PDA-coated fabric shows that the spectra at 3368 and 2850 cm −1 of PDA overlapped on the fabric absorption spectrum, demonstrating the successful growth of PDA in the as-prepared PDANSs@fabric. 38,39…”
Section: Resultsmentioning
confidence: 99%